Froggy juega al fútbol - London, Jonathan, 1947-; Remkiewicz, Frank; Pasternac, Susana (New York : Scholastic Inc., 2000)
Although Froggy is very excited when his Dream Team plays for the city soccer championship, he makes a mistake on the field that almost costs the team the game.
Accelerated Reader AR
Keywords: Soccer -- Fiction; Frogs -- Fiction; Animals -- Fiction; Spanish language materials